2023
DOI: 10.1186/s12957-023-03046-1
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative and oncologic outcomes of transperitoneal versus retroperitoneal laparoscopic nephroureterectomy for upper urinary tract urothelial carcinoma: a systematic review and pooled analysis of comparative outcomes

Abstract: Background The debate on whether to choose a transperitoneal (TP) or retroperitoneal (RP) approach for treating upper urinary tract urothelial carcinoma (UTUC) with laparoscopic surgery has been drawing attention. This study aimed to systematically review and meta-analyze the existing evidence regarding oncologic and perioperative outcomes of transperitoneal laparoscopic radical nephroureterectomy (TLNU) and retroperitoneal laparoscopic radical nephroureterectomy (RLNU) in managing UTUC. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Zhu et al conducted a review of tLNUs and rLNUs [ 15 ]. The results showed that the tLNU group had a significantly shorter operative time, a significantly longer recovery time of intestinal function, and no significant differences in the estimated blood loss, length of stay, visual analog pain scale, or overall complication rates.…”
Section: Discussionmentioning
confidence: 99%
“…Zhu et al conducted a review of tLNUs and rLNUs [ 15 ]. The results showed that the tLNU group had a significantly shorter operative time, a significantly longer recovery time of intestinal function, and no significant differences in the estimated blood loss, length of stay, visual analog pain scale, or overall complication rates.…”
Section: Discussionmentioning
confidence: 99%
“…Radical nephroureterectomy using the retroperitoneal approach has various advantages such as direct access to the renal hilum, avoidance of the need for bowel mobilization, prevention of bowel complications, and faster postoperative recovery 1 . For this reason, the retroperitoneal approach has been widely used in laparoscopic surgery; however, BCE has often been performed by open surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Radical nephroureterectomy with bladder cuff excision (BCE) is the gold standard treatment for high‐grade upper tract urothelial carcinomas. Compared with the transperitoneal approach, the retroperitoneal approach has the advantages of not requiring mobilization of the bowel and intraperitoneal organs and faster postoperative recovery of intestinal function 1 …”
Section: Introductionmentioning
confidence: 99%